Developmental performance of hospitalized severely acutely malnourished under-six children in low- income setting - Teklu Gemechu Abessa; Liesbeth Bruckers; Patrick Kolsteren; Marita Granitzer (BMC, 2017)
Abstract Background Retrospective studies show that severe acute malnutrition (SAM) affects child development. However, to what extent SAM affects children of different ages at its acute stage is not well documented. This study was aimed at comparing the developmental performance of severely acutely malnourished children under six with that of age and gender-matched non-malnourished healthy children. Methods The developmental performances of 310 children with SAM (male = 155, female = 155); mean age = 30.7 mo; SD = 15.2 mo) admitted to the nutritional rehabilitation unit (NRU) at Jimma University's Hospital was compared with that of 310 age and gender-matched, non-malnourished healthy children (male = 155, female = 155; mean age = 29.6 mo; SD = 15.4 mo) living in Jimma Town in Ethiopia. Two culturally adapted tools were used: (1) the Denver II-Jimma, to assess the children's performance on personal social (PS), fine motor (FM) language (LA), gross motor (GM) skills, and (2) the Ages and Stages Questionnaires: Social-Emotional (ASQ:SE), to assess social-emotional (SE) skills. Multivariable Poisson regression analysis was conducted to compare the developmental performance scores of SAM and non-malnourished children. Results For one-year-old children, SAM delays their developmental performance on GM, FM, PS and LA by 300%, 200%, 140% and 71.4% respectively. For three-years-old children, SAM delays their developmental performance on GM by 80%, on FM and LA by 50% each, and on PS by 28.6%. Of the skills assessed on Denver II-Jimma, GM is the most, and PS is the least affected. Younger SAM children are more affected than older ones on all the domains of development. The delay in FM, GM, LA and PS generally decreases with an increase in age. Social-emotional behavior problems seem to be most pronounced in the very young and older age ranges. Conclusions SAM has a differential age effect on the different dimensions of development in children under 6 years of age.